A broadband piezoelectric energy harvester with movable mass for frequency active self-tuning. (1st April 2020) - Shi, Ge; Yang, Yanmei; Chen, Junfu; Peng, Yansheng; Xia, Huakang; Xia, Yinshui
Abstract: A broadband active self-tuning frequency piezoelectric energy harvester (AST-PEH) is proposed in this paper. It consists of a piezoelectric cantilever beam, an energy harvesting and control circuit (EHCC), a miniature stepper motor, a screw rod and a T-section mass. It can actively adjust the position of the T-section mass according to the ambient vibration frequency. It matches the AST-PEH's resonant frequency with the ambient vibration excitation frequency, and it widens the operating frequency range of the AST-PEH. The expression of the AST-PEH's resonant frequency function is constructed based on the dynamic and static theoretical analysis. The theoretical model of the AST-PEH under different position of the T-section mass is analyzed by ANSYS15.0 APDL, which is verified by two different materials and sizes. The tested two type substrate materials are steel and polylactic acid (PLA). The experimental results show that the frequency range of the two type harvesters are 4.8 Hz–6.3 Hz and 8.17 Hz–14.3 Hz respectively, and the widening rates of the working frequency are 31.25% and 75% respectively. The tested maximum output power of steel type AST-PEH is 0.32 mW at 6.3 Hz under 0.32 g acceleration and with a 100 KΩ load resistance.